JUVENILE RHEUMATOID ARTHRITIS (TERMINOLOGICALAND CLASSIFICATION ASPECTS) - N N Kuzmina; A V Shaikov (Научно-практическая ревматология)
Basing on the data of home and foreign literature and on the long-term experience of pediatric rheumatologists, terminologic and classification aspects of Juvenile rheumatoid arthritis (JRA) are presented. Approaches to developing of diagnostic and classification of JRA criteria in future are described.